Effect of Immunotropic Substances on the Functional Activity of Neutrophils - Aljwaid, Seger Abdulkhadim Seger; Alaboudi, Mohammed Ali (Manajemen Pelayanan Kesehatan, 2024)
This work investigates the effects of amino acids, in particular zinc aspartate and arginine, on neutrophil functional activity in the presence of oxidative stress. Amino acids are recognized to be beneficial for a number of body processes, but little is known about how they regulate neutrophil activity. We measured immunoglobulin levels pre- and post-treatment, neutrophil metabolic activity, and phagocyte activity in a sample of patients with chronic renal illness, aged 20 to 60. The immunological status significantly improved, as evidenced by higher neutrophil metabolic activity and phagocytosis indices. These results imply that taking supplements of amino acids may improve immune responses, which may have therapeutic ramifications for the treatment of chronic inflammatory diseases.